2013
DOI: 10.1016/j.aap.2012.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Short and user-friendly: The development and validation of the Mini-DBQ

Abstract: The Driver Behavior Questionnaire (DBQ) is used to measure aberrant driver behavior by asking drivers how often they engage in various aberrant driver behaviors. Since the development of the original DBQ, several modified versions have been developed. The difference between the various versions is that new items are added or existing items modified or excluded. However, despite the differences, all versions are relatively long and therefore time-consuming and tiring to answer, which might limit the usability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The inclusion of different aspects related to riding style and road user behaviour, such as a standardised measurement of violations, errors and lapses (cf. Martinussen et al, 2013) would give more insight into this and is suggested for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of different aspects related to riding style and road user behaviour, such as a standardised measurement of violations, errors and lapses (cf. Martinussen et al, 2013) would give more insight into this and is suggested for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 8 DBQ (Martinussen et al, 2013) has items, like "Getting involved in unofficial "races" with other car drivers", "Forgetting where you left your car in a multi-level car park" or "Getting into the wrong lane at a roundabout or approaching a road junction", all of which are less relevant behaviours for PDs. The items that we decided to include are relevant because they deal with behaviours that may stem from doing monotonous tasks, such as driving on a highway.…”
Section: Page 8 Of 15mentioning
confidence: 99%
“…The meta-analysis of De Winter & Dodou (2010) showed that these two factors can be used as common denominators for the various factor structures encountered in the literature. This is a noteworthy finding because the instrument comes in many versions, comprising anything from 10 (Martinussen, Lajunen, Møller, & Özkan, 2013) to 112 (Kontogiannis et al, 2002) items. The basic distinction between voluntary and involuntary forms of traffic behavior has its roots in the theory of errors presented in Reason (1990).…”
mentioning
confidence: 90%